2019
DOI: 10.3102/0091732x18821123
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Informed Practices in Schools Across Two Decades: An Interdisciplinary Review of Research

Abstract: Attention to childhood trauma and the need for trauma-informed care has contributed to the emerging discourse in schools related to teaching practices, school climate, and the delivery of trauma-related in-service and preservice teacher education. However, though trauma-informed systems of care include schools, empirical work informing trauma-informed teaching and teacher education that is reflected back to those audiences is less established. This interdisciplinary overview and synthesis of literature examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
158
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(221 citation statements)
references
References 57 publications
(106 reference statements)
1
158
0
12
Order By: Relevance
“…A third macrolevel support refers to various intervention programs aimed at mitigating the impact of youth trauma (Ford, Steinberg, et al, 2012; Scheeringa et al, 2011). Indeed, to synthesize three recent systematic reviews of school-based intervention programs across 171 articles (with some overlapping studies), it appears that long-term programs with a codified curriculum that is co-constructed with caregivers and delivered by trained staff are most effective, although what is still needed are better frameworks for implementing and measuring effectiveness of said programs and protocols for more precise analysis of participant demographics (Rodger et al, 2019; Thomas et al, 2019; Yohannan & Carlson, 2019). Unfortunately, I found that when the primary focus is on investigating the best program intervention, studies minimize underlying racialization problems or imply that race is inconsequential to understanding and responding to students’ trauma-related experiences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A third macrolevel support refers to various intervention programs aimed at mitigating the impact of youth trauma (Ford, Steinberg, et al, 2012; Scheeringa et al, 2011). Indeed, to synthesize three recent systematic reviews of school-based intervention programs across 171 articles (with some overlapping studies), it appears that long-term programs with a codified curriculum that is co-constructed with caregivers and delivered by trained staff are most effective, although what is still needed are better frameworks for implementing and measuring effectiveness of said programs and protocols for more precise analysis of participant demographics (Rodger et al, 2019; Thomas et al, 2019; Yohannan & Carlson, 2019). Unfortunately, I found that when the primary focus is on investigating the best program intervention, studies minimize underlying racialization problems or imply that race is inconsequential to understanding and responding to students’ trauma-related experiences.…”
Section: Resultsmentioning
confidence: 99%
“…However, the first of these reviews stressed a critical need to understand and recognize the impact of youth trauma on school functioning (De Pedro et al, 2011; McBrien, 2005; Perfect et al, 2016; Sullivan & Simonson, 2016). Additionally, subsequent systematic reviews on youth trauma have contributed to the body of scholarship by exploring effective trauma-based interventions; in short, these reviews have recommended that trauma-based interventions (a) use codified curricula that are co-constructed with caregivers for contextual specificity, (b) be delivered by trained staff, and (c) incorporate more intersectional data points for analyses of program and student success outcomes (Rodger et al, 2019; Thomas et al, 2019; Yohannan & Carlson, 2019). Collectively, this growing body of scholarship on youth trauma in educational contexts has generated sizeable concern among school-based actors, while also underscoring a need for stronger interdisciplinary work that can advance future discoveries about equitable resources, programs, and practices for improving success outcomes among trauma-exposed youth in U.S. schools.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…48 Whereas little is known about the impact of whole-school trauma-informed strategies, there is significant empirical support for clinical interventions for those identified as needing support in tiers 2 and 3 of a MTSS. 41,45 For example, cognitive behavioral interventions for trauma in schools and trauma-focused cognitive behavioral therapy are well-established with multiple rigorous evaluations. 19 However, such targeted approaches may not be able to serve the needs of all students who are experiencing trauma.…”
Section: School-based Trauma-informed Framework and Programsmentioning
confidence: 99%
“…Recent reviews of trauma‐informed approaches in schools have all concluded that there is a dearth of evidence about what works for nonclinical staff. That is not to say that there is a lack of guidance on best practices; rather, very little of the guidance references strong evidence 19,41 . Previously, most research focused on educators examined efforts to build knowledge around the effects of trauma and to link students to more targeted interventions and supports 41 .…”
Section: Literature Reviewmentioning
confidence: 99%